Shared Stories of Successful Graduates of Juvenile Residential Programs - Mincey, Barrett; Maldonado, Nancy; Lacey, Candace (LEARNing Landscapes, 2012)
This phenomenological study explored stories of successful graduates of residential programs regarding their experiences while in treatment. Participants were purposefully selected. Data were collected through audio-taped interviews and analyzed for themes. Shared stories indicated the impact of counselors, negative and positive aspects of programs, and peer relationships.